Self-reported and Accelerometer-Measured Physical Activity in Children With Cardiomyopathy. Issue 3 (May 2020) - Cunningham, Chentel; Spence, John C.; Stearns, Jodie A.; Carson, Valerie; Kantor, Paul F.; Urschel, Simon; Conway, Jennifer
Abstract : Purpose: Children with cardiomyopathy are at risk of heart failure with reduced physical activity (PA) as a cardinal manifestation. Clinical assessment of PA in children is challenging due to the limited validity of subjective reports. The aim of the study was to compare accelerometery measurement with parental report and to identify factors associated with movement behavior (PA, sedentary time, steps per day). Method: Fifteen patients with cardiomyopathy (mean, 9.7 years; 64% male) were asked to wear an Actigraph GT3X accelerometer in Edmonton, Canada. Demographics, clinical characteristics, parental-reported PA, and health-related quality of life data were also collected. Results: Participants engaged in a median of 38 minutes of moderate-vigorous PA per day with higher levels in boys versus girls (73.9 [25.03, 78.91] vs 4.13 [2.53, 37.67] minutes, P = .03). Children participating in recreational sports showed a higher level of moderate-vigorous PA (73.92 min/d) compared with those who did not participate (73.9 vs 22.7 min/d, P = .05), and positive family outlook on the child's health was associated with less sedentary time ( P = .04). Conclusion: Accelerometer measurement in children with cardiomyopathy is an achievable and more objective measure of PA compared with parental report alone and highlighted low levels of PA among these children.